The Transcriptional Factor PPARαb Positively Regulates Elovl5 Elongase in Golden Pompano Trachinotus ovatus (Linnaeus 1758) - Zhu, Ke-Cheng; Song, Ling; Zhao, Chao-Ping; Guo, Hua-Yang; Zhang, Nan; Guo, Liang; Liu, Bao-Suo; Jiang, Shi-Gui; Zhang, Dian-Chang (Frontiers in Physiology, 2018)
The nuclear peroxisome proliferator-activated receptors (PPARs) regulate the transcription of elongation of very long-chain fatty acid (Elovl), which is involved in polyunsaturated fatty acid (PUFA) biosynthesis in mammals. In the present study, we first characterized the function of Elovl5 elongase, which was a rate-limiting enzyme in Trachinotus ovatus. Functional study showed that ToElovl5, displayed high elongation activity towards C18 and C20 PUFA. To investigate whether PPARαb was a regulator of Elovl5, we second reported the sequence of T. ovatus PPARαb (ToPPARαb). The open reading frame (ORF) sequence encoded 469 amino acids possessing four typical characteristic domains, including an N-terminal hypervariable region, a DNA-binding domain (DBD), a flexible hinge domain and a ligand-binding domain (LBD). Third, promoter activity experiments showed that the region from PGL3-basic-Elovl5-5 (-146 bp to +459 bp) was defined as the core promoter by progressive deletion mutation of Elovl5. Moreover, PPARαb overexpression led to a clear time-dependent enhancement of ToElovl5 promoter expression in HEK 293T cells. Fourth, the agonist of PPARαb prominently increased PPARαb and Elovl5 expression, while PPARαb depletion by RNAi or an inhibitor was correlated with a significant reduction of Elovl5 transcription in T. ovatus caudal fin cells (TOCF). In conclusion, the present study provides the first evidence of the positive regulation of Elovl5 transcription by PPARαb and contributes to a better understanding of the transcriptional mechanism of PPARαb in fish.